Pandarella - Guillain, Charlotte; Beacon, Dawn; Perrault, Charles (Chicago, Ill Raintree, 2013)
A simplified version of the familiar fairy tale featuring a panda who, with help from her furry godmother, attends a ball and dances with a handsome prince. Includes a note on the history of the tale
A gift from book Africa
English stories
1 2 13 15
Keywords: Fairy tales; Pandas -- Juvenile fiction